CAREER DEVELOPMENT CENTER (CDC) SEBAGAI STRATEGI UNGGULAN DALAM MEWUJUDKAN PENGEMBANGAN KARIR MAHASISWA DI UNIVERSITAS UDAYANA - Sihombing, Tulus P; Dwi Wismayanti, Kadek Wiwin; Sastra Wijaya, Komang Adi (CITIZEN CHARTER; Vol 1 No 2 (2019), 2019)
ABS TRACT   Career Development Center ( CDC) i s a Career Development Center for s tudents at Udayana University. T his program a i ms to develop s tudents' c areer and s oft sk ill s with v arious programs i n order t o i m prove t he c o mpetency of Human Resources ( HR). Fr om the r esults of t he S W O T analysis, i t was f ound t hat t he CDC h as a problem i n r ealizing a s trategy focused on t he i ss ue of employee r esources ( HR), l ow b udget f unds and l ack of facilities to s u pport activities. T h erefore r esearchers provide and r e c ommend a New P u blic Management Managerial to s treamline the r ealization o f the CDC s trategy. In r e alizing this New Managerial P u blic M a nagement there are s everal   i ndicators    i ncluding,   T h e   Drive   Or i e ntation,   D ownsizing    and   D ecentralization Or i entation, Ori entation i n S e arch of E xc ellence, and P u blic S ervice Or i e ntation, which emphasizes the q uality, m iss i on and v alues to be achieved by p ublic organizations.   Keywords: S trategy   M an agement, H uman   Resource Management, New   P u blic   Managerial Management, CDC (Career Development Center)